2012
DOI: 10.1093/icvts/ivs328
|View full text |Cite
|
Sign up to set email alerts
|

Congenital pericardial defect with ruptured acute type A aortic dissection

Abstract: We report 2 cases of congenital pericardial defect with ruptured acute type A aortic dissection. Case 1: An 83-year old man presented with sudden chest and back pain, and computed tomography (CT) showed acute aortic dissection with left pleural massive effusion. Because of his unstable haemodynamic condition with low blood pressure, an emergency operation was performed. We observed small amounts of bloody pericardial effusion, massive left-sided bloody pleural effusion and a partial left-sided pericardial defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 3 publications
0
7
0
1
Order By: Relevance
“…Approximately one-third of congenital absence of pericardium cases are associated with other congenital heart abnormalities such as mitral stenosis, tetralogy of Fallot, atrial septal defect (ASD), bicuspid aortic valve, diaphragmatic hernia, an anomaly of the aortic arch leading to type A aortic dissection, annuloaortic ectasia, marfanoid features, congestive heart failure secondary to aortic insufficiency and myocardial non-compaction 8–11. The defect due to aberrant development of the septum transversum is associated with a defect in the central tendon of the diaphragm 12.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately one-third of congenital absence of pericardium cases are associated with other congenital heart abnormalities such as mitral stenosis, tetralogy of Fallot, atrial septal defect (ASD), bicuspid aortic valve, diaphragmatic hernia, an anomaly of the aortic arch leading to type A aortic dissection, annuloaortic ectasia, marfanoid features, congestive heart failure secondary to aortic insufficiency and myocardial non-compaction 8–11. The defect due to aberrant development of the septum transversum is associated with a defect in the central tendon of the diaphragm 12.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac displacement and increased mobility impose an increased risk for traumatic type A aortic dissections 12. Acute type A dissection associated with hemothorax and with little pericardial effusion indicates existence of a pericardial defect 9. If an acute dissection occurs in a patient with an undiagnosed CPD, the diagnosis of dissection may not be recognised due to the absence of significant pericardial effusion 9…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have previously reported ruptured acute aortic dissection cases associated with a partial or complete congenital pericardial defect [2][3][4][5][6]. However, those cases involved little or no pericardial effusion with massive left hemothorax.…”
Section: Discussionmentioning
confidence: 99%
“…PMCT initially exhibited a hematoma in the false lumen of the ascending aorta with a slight hemopericardium and a large amount of left hemothorax as well as focal pericardial dimpling and discontinuity around the left ventricle. Previous studies have described problematic conditions, such as a congenital pericardial defect associated with intrapericardial hemorrhage and a left hemothorax [12][13][14][15]. A congenital pericardial defect is usually found more frequently on the left side of the heart [25] and is characterized by a round to oval-shape with a smooth and thickened rim [26].…”
Section: Discussionmentioning
confidence: 99%
“…A hemothorax also occurs in some AoD cases, and most cases are considered to be the result of a rupture in the descending aorta [7][8][9]. Other cases have had an unusual presentation of a left pleural effusion complicated by AoD [10,11] or a congenital pericardial defect with ruptured type A AoD [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%